Design for assembly and application using Boothroyd Dewhurst method - Muhammad Safuan, Othman (2010)
This paper shows a detailed study to investigate the efficiency of Boothroyd Dewhurst Design for Assembly (DFA) method that was applied to improve the product design process. In today competitive world, companies try to cut down the manufacturing cost and at the same time increase their profit. In order to be a competent player in the market, the product should arrive into market within a short time and reasonable price. Assembly cost is one of the major operations in manufacturing but always ignored during designing stage. In this study, comparative analysis was done between current and alternative design. The design was done by using Solidwork software and analyzed by using manual and DFA software analysis to get the efficiency of current design. Then, by applying Boothroyd Dewhurst DFA method guideline, alternative design was generated and analyzed using the same method to compare the effectiveness of this new alternative design. From the study, it was found that the design efficiency increased from 16.7% to 46.4% when Boothroyd Dewhurst DFA method was applied. The time of assemble also decreased from 193.09 seconds to 58.48 seconds per product. From the result, it was proven that this Boothroyd Dewhurst DFA method was able to improve the design in terms of design efficiency, product assemble time and labor cost. This method can be applied in manufacturing company in order to improve their design effectiveness